Learning Physics Using Search, Solve, Create, Share and Preview, Question, Read, Reflect, Recite, Review Models Analyzed from Critical Thinking and Problem-solving Skills on Student Learning Outcomes - Santi Eka Ambaryani*; Sarwanto Sarwanto; Sri Budiawanti (Jurnal Pendidikan Sains Indonesia, 2022)
Problem in this research is students’ critical thinking and problem solving skills on learning physics still in low category. The aim of this research is to determine the effect of applying SSCS and PQ4R models, the effect of critical thinking and problem solving skills and their interactions on student learning outcomes. The research used an experimental method and a scientific approach with the research population of all students of class XI IPA SMAN 1 Karanganyar in the 2021/2022. The research sample was determined by cluster random sampling. The experimental class 1 is class XI IPA3 with SSCS model, while experimental class 2 is class XI IPA4 with PQ4R model. The data collection technique used the test method for student learning outcomes data while the questionnaire method for data on students' critical thinking skills and problem solving skills. The data analysis technique used the Anova test. The results concluded that (1) there is a difference in learning outcomes between students who apply SSCS and PQ4R models, learning outcomes where high critical thinking and problem solving student have better outcome than the low one, (2) there is an interaction between learning models, critical thinking and problem solving skills on student learning outcomes.